DIFFERENTIAL DIAGNOSIS OF IRON DEFICIENCY ANEMIA AND BETA THALASSEMIA IN PORT HARCOURT PREGNANT WOMEN USING THE MENTZER INDEX - Jacob, Ransom; Aboko, Princess; Eze, Evelyn; Jeremiah, Zaccheaus (Sanamed, 2024)
Introduction: The Mentzer index is a cost-effective and accurate method for differentiating between iron deficiency anemia (IDA) and beta-thal[1]assemia. Anemia in pregnancy is a global health concern, especially in developing countries like Nigeria, where it is primarily linked to iron deficiency and may also include other underlying hemoglobin disorders, with beta-thalassemia (βT) being the most common. This cross-sectional study aimed to differentiate between iron deficiency anemia and beta-thalassemia in pregnant women attending tertiary hospitals in Port Harcourt, Nigeria, based on the Mentzer Index. Materials and Methods: A total of 120 apparently healthy pregnant women aged between 20 and 50 years were recruited for the study. Five milliliters (5 ml) of venous blood were collected from each participant using a disposable syringe and placed into an ethylene diamine tetraacetic acid (EDTA) anticoagulated bottle for full blood count determination using a Mindray automated analyzer. The Mentzer Index was calculated from the mean cell volume (MCV) and red blood cell (RBC) count values. The data obtained were analyzed statistically using Statistical Package for Social Sciences (SPSS) Version 23. Results: Mean age ± SD of the study population (28.68 ± 5.6 years), Mean + SD of Hb (11.38 + 2.08g/ dl), PCV (31.72 + 4.59%), RBC count (4.65 ± 1.86 x 1012/L), MCV (79.92 ± 5.91 fl) and Platelets count (272.9 ± 42.10 x 109 /L) respectively. Out of 120 participants, 48 (40%) had Hb and PCV values above 11.0 g/dl and 33% respectively. A total of 5 (4.17%) had a Mentzer index < 13 and confirmed beta-thalassaemia, while 67 (55.83%) had a Mentzer index > 13 and confirmed iron-deficiency anaemia indicating a 60% prevalance of anaemia in study population with iron-deficiency anaemia been more common amongst the study population than beta-thalassaemia. Conclusion: Based on the Mentzer Index calculation, this study revealed a high prevalence of iron deficiency anemia (IDA) and a lower prevalence of beta-thalassemia among pregnant women attending tertiary hospitals in Port Harcourt, Nigeria. Healthcare practitioners should consider incorporating the Mentzer Index as a cost-effective means of differentiating iron deficiency anemia from beta-thalassemia in pregnant women, particularly in rural areas. Additionally, increased awareness and educational programs focusing on proper nutrition and iron supplementation during pregnancy should be advocated.
Keywords: Mentzer Index; Iron deficiency Anaemia; Beta-thalassaemia; Pregnant Women